PRO-AKTIF (PROGRAM ADVOKASI DAN EDUKASI PREVENTIF): SOSIALISASI BAHAYA NARKOBA DALAM MEMBANGUN KETAHANAN DIRI SISWA SMA NEGERI 2 KENDARI - Nita Trinovitasari; Muhammad Arba; Yayat Jatnika; Nur Arsianti Azizah; Sitti Hadijah; Fitri Shafariyah; Arni Asmarani Salda (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Drug abuse amongst teenagers poses a serious threat to the future of the younger generation. This community service initiative, entitled PRO-AKTIF (Preventive Advocacy and Education Programme): Raising Awareness of the Dangers of Drugs to Build Resilience amongst Students at SMAN 2 Kendari, aims to enhance students’ knowledge of the types of drugs, their effects, the signs of abuse, and the skills needed to refuse offers of drugs, as well as to enable them to disseminate positive information to their peers. The activity took place on 10 June 2026 and involved a drug counsellor from the Southeast Sulawesi Provincial Office of the National Narcotics Agency (BNN) and 34 student council members from SMAN 2 Kendari. The awareness-raising session employed an educational and participatory approach, combining counselling methods with interactive and reflective activities. The education was delivered using presentations, videos and leaflets. The evaluation tool consisted of a questionnaire administered before and after the intervention, with the data subsequently analysed quantitatively. The results of the analysis showed a significant increase in awareness and knowledge regarding drugs following the awareness-raising session. This activity was effective in enhancing students’ resilience through an understanding of the dangers of drugs; it is therefore recommended that it be carried out on an ongoing basis.